Analisis Faktor-faktor Resiko terhadap kejadian Stunting pada Balita (0-59 bulan) di Puskesmas Wae Mbeleng - Afrinita, Maria; Banul, Maria Sriana; Purba, Nurhaida; Hamat, Viviana (Universitas Malahayati, 2025)
ABSTRACT Stunting is a chronic nutritional problem that impairs the growth and development of children and remains a major challenge in developing countries, including Indonesia. East Nusa Tenggara (NTT) Province, particularly Manggarai District, records a very high prevalence of stunting. The causes of stunting are multifactorial, involving both direct and indirect factors such as inadequate parenting, poor nutritional status, and low socioeconomic conditions. This study aims to analyze the risk factors associated with the incidence of stunting among children aged 0–59 months in the working area of Wae Mbeleng Public Health Center, Manggarai District. This is a quantitative study with a cross-sectional design. Data were collected through observation, interviews, and document review. Univariate and bivariate analyses were conducted to assess the relationships between parenting patterns, nutritional status, and economic status with stunting incidence. The majority of respondents (63.3%) practiced poor parenting, and all children raised under these conditions were stunted (p = 0.000). Additionally, 40% of children had poor nutritional status, and all of them were stunted (p = 0.000). Economically, 76.7% of families were in the low-income category, and all children from these families were also stunted (p = 0.000). All three factors showed a very significant association with stunting. Stunting among children at Wae Mbeleng Health Center is significantly influenced by inadequate parenting, poor nutritional status, and low family economic conditions. Effective stunting prevention requires integrated and multisectoral interventions focused on parenting education, nutritional improvement, and family economic empowerment. Keywords: Stunting, Parenting, Nutritional Status, Economic Status, Children Under Five, Manggarai. ABSTRAK Stunting merupakan masalah gizi kronis yang menghambat pertumbuhan dan perkembangan anak, dan menjadi tantangan besar di negara berkembang, termasuk Indonesia. Provinsi Nusa Tenggara Timur (NTT), khususnya Kabupaten Manggarai, mencatat prevalensi stunting yang sangat tinggi. Stunting disebabkan oleh berbagai faktor langsung maupun tidak langsung, antara lain pola asuh yang tidak tepat, status gizi yang buruk, dan kondisi sosial ekonomi yang rendah. Penelitian ini bertujuan untuk menganalisis faktor-faktor risiko yang berhubungan dengan kejadian stunting pada balita usia 0–59 bulan di wilayah kerja Puskesmas Wae Mbeleng, Kabupaten Manggarai.Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Data dikumpulkan melalui observasi, wawancara, dan telaah dokumen. Analisis dilakukan secara univariat dan bivariat untuk melihat hubungan antara variabel pola asuh, status gizi, dan status ekonomi dengan kejadian stunting. Sebagian besar responden (63,3%) menerapkan pola asuh yang tidak baik dan seluruh anak yang diasuh dengan pola ini mengalami stunting (p = 0,000). Selain itu, 40% balita memiliki status gizi kurang, dan seluruhnya mengalami stunting (p = 0,000). Dari sisi ekonomi, 76,7% keluarga berada pada kategori ekonomi rendah, dan anak-anak dari kelompok ini seluruhnya mengalami stunting (p = 0,000). Ketiga faktor tersebut menunjukkan hubungan yang sangat signifikan terhadap kejadian stunting. Kejadian stunting di Puskesmas Wae Mbeleng dipengaruhi secara signifikan oleh pola asuh yang tidak memadai, status gizi yang buruk, dan kondisi ekonomi keluarga yang rendah. Pencegahan stunting memerlukan intervensi terpadu dan multisektoral, dengan fokus pada edukasi pengasuhan anak, peningkatan status gizi, dan pemberdayaan ekonomi keluarga. Kata Kunci: Stunting, Pola Asuh, Status Gizi, Status Ekonomi, Balita, Manggarai